Industrialisation and everyday life - Braun, Rudolf 1930-2012 (Cambridge University Press, 2005)
Industrialising und Volksleben by Rudolf Braun is widely regarded as a classic of modern social history, inspiring a whole series of profound debates about the transition from pre-industrial society to the modern world. Utilising evidence from an upland Swiss canton, Industrialisation and Everyday Life provides a comprehensive survey of the impact upon popular life styles of the development of widespread cottage industry, as land-hungry labourers added textile manufacture to their existing agricultural concerns. Professor Braun analyses the structure of such 'proto-industry', looking at the changes wrought upon family life, domestic housing and popular culture in general. A great variety of literary and artistic sources are drawn together in a vivid portrayal of the ways in which early industrial development and social modernisation became fused together